Short Term Effect of Calcium Hydroxide, Mineral Trioxide Aggregate and Calcium-Enriched Mixture Cement on the Strength of Bovine Root Dentin - sahebi, safoora; dolatkhah, vahid; moazami, fariborz; nabavizade, mohammadreza (Iranian Endodontic Journal, 2012)
Introduction: Some studies in dental literature have proposed that short term and long term exposure of root dentin to calcium hydroxide predisposes it to fracture. Mineral trioxide aggregate (MTA) and a recently introduced endodontic material, calcium-enriched mixture (CEM) cement may be used instead of calcium hydroxide and might have an effect on the strength of root dentin. Therefore, the aim of this in vitro study was to compare the short-term effect of calcium hydroxide, MTA and CEM cement on the strength of bovine root dentin. Materials and Methods: In this experimental study, 15 freshly extracted intact bovine incisors were selected. A cylinder with uniform wall thickness (internal diameter of 2.5 and external diameter of 5.5) was prepared. The cylinders were cut longitudinally into 4 symmetrical pieces. The 60 prepared samples were divided into four groups (n =15). The samples were placed in 4 petri-dishes containing calcium hydroxide, MTA, CEM cement and normal saline as the control group. They were then subjected to flexural forces applied by Instron universal machine. Data was analyzed using ANOVA and Tukey test. Results: The mean flexural force in the calcium hydroxide, MTA and CEM cement groups was significantly lower than that in the control teeth (77.9 N, 90.66 N, 94.40 N, compared to 125.12 N respectively, P=0.001). There were no significant differences between calcium hydroxide, MTA and CEM cement group. <span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Conclusion<span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">: MTA and CEM cement decreased the flexural strength of bovine root dentin, like their counterpart calcium hydroxide. Further studies are required to determine the effect of these materials on human root dentin clinically.